2022
DOI: 10.16899/jcm.1004825
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of A Weight-Loss Diet in Women Doing Reformer Pilates: A 12-Week Evaluation

Abstract: Aim: This study aims to define the effect of a weight-loss diet on body composition in women doing reformer pilates for 12 weeks. It compares dietary habits in subject groups with and without a weight-loss diet and macro and micronutrient intakes at the beginning and end of the study. Method: A total of 49 women (≥18 age) were randomly allocated to either a control (CG: reformer pilates; n=23) or a study (SG: reformer pilates+weight-loss diet; n=26) group. In both groups, subjects did pilates for 45 minutes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The aim of Pilates exercises is to protect general health, improve posture and coordination by increasing body flexibility, muscle strength, dynamic and static balance (6). Studies have reported that regular Pilates exercises with or without equipment improve sleep quality in obese and overweight individuals (11), reduce injuries caused by falls by improving balance (26), and give positive results on body composition by reducing body fat (20).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of Pilates exercises is to protect general health, improve posture and coordination by increasing body flexibility, muscle strength, dynamic and static balance (6). Studies have reported that regular Pilates exercises with or without equipment improve sleep quality in obese and overweight individuals (11), reduce injuries caused by falls by improving balance (26), and give positive results on body composition by reducing body fat (20).…”
Section: Introductionmentioning
confidence: 99%